Anti-Angiogenic Efficacy of PSORI-CM02 and the Associated Mechanism in Psoriasis In Vitro and In Vivo - Lu, Yue; Yang, Yuqi; Zhang, Junhong; Zhang, Hongyu; Ma, Changju; Tang, Xiaojuan; Wu, Jingjing; Li, Li; Wei, Jianan; Chen, Haiming; Lu, Chuanjian; Han, Ling (Frontiers in Immunology, 2021)
Psoriasis is a chronic proliferative autoimmune dermatologic disease characterised by abnormal angiogenesis. Thus, regulating angiogenesis in the skin is an important treatment strategy for psoriasis. PSORI-CM02, an empirical Chinese medicine formula optimised from Yin Xie Ling, was created by the Chinese medicine specialist, Guo-Wei Xuan. Clinical studies have shown that PSORI-CM02 is safe and effective for the treatment of psoriasis. However, its anti-psoriatic mechanisms remain to be further explored. In this study, we investigated the effects of PSORI-CM02 on angiogenesis in the skin and the underlying mechanisms in IL-17A-stimulated human umbilical vein endothelial cells (HUVECs) and a murine model of imiquimod (IMQ)-induced psoriasis. In vitro, PSORI-CM02 significantly inhibited the proliferation and migration of IL-17A-stimulated HUVECs in a dose-dependent manner. Further, it markedly regulated the antioxidative/oxidative status and inflammation; suppressed the expression of VEGF, VEGFR1, VEGFR2, ANG1, and HIF-1α; and reduced the phosphorylation of MAPK signalling pathway components in IL-17A-stimulated HUVECs. In vivo studies showed that PSORI-CM02 markedly reduced angiogenesis in the skin of mice with IMQ-induced psoriasis, while significantly rebalancing antioxidant/oxidant levels; inhibiting the production of IL-6, TNF-α, IL-17A, and IL-17F; and repressing the synthesis of angiogenic mediators. In addition, PSORI-CM02 markedly reduced the activation of the MAPK signalling pathway in psoriatic skin tissue. Taken together, our results demonstrated that PSORI-CM02 inhibited psoriatic angiogenesis by reducing the oxidative status and inflammation, suppressing the expression of angiogenesis-related molecules, and inhibiting the activation of the MAPK signalling pathway in vitro and in vivo.